PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN WHITEBOARD ANIMATION PADA GURU-GURU MGMP MATEMATIKA SMP KOTA PEKALONGAN - Syita Fatih ‘Adna; Nur Baiti Nasution (Universitas PGRI Yogyakarta, 2021)
Mathematics is one of the compulsory subjects in the junior high school education unit. The presentation of Mathematics learning is not supported by creative learning media that utilize the latest technology. The challenge of teachers facing the 4.0 revolution, namely junior high school teachers must be able to utilize technology in learning in addition to varying interactive learning models. The objectives of this training are (1) to introduce mathematics teachers to the use of Animated Chalkboard that can be used as learning media, (2) to improve the ability of Mathematics teachers to create Mathematics learning media using Animation Chalkboard, (3) to produce Mathematics learning media products Middle school uploaded via social media youtube. The training for Pekalongan City Middle School Mathematics teachers was held for three months. The methods used in this activity are (1) Socialization of the use of Animated Whiteboards as a medium of Mathematics learning, (2) assistance in making Mathematics learning media using Animated Whiteboards, (3) evaluation of instructional media products and training activities. The results obtained are an increase in the ability of teachers to create Mathematics learning media using Animation Chalkboards and increase learning media products uploaded to YouTube that can be utilized by Junior High School Mathematics teachers in learning. The product produced is Mathematics learning media that has been uploaded on YouTube social media.